A novel protocol to prepare cell probes for the quantification of microbial adhesion and biofilm initiation on structured bioinspired surfaces using AFM for single‐cell force spectroscopy: Dedicated to Prof. em. Dr. Dr. H.C. Karl Schügerl on the occasion of his 90th birthday. Issue 8 (7th June 2017) - Mulansky, Susan; Saballus, Martin; Friedrichs, Jens; Bley, Thomas; Boschke, Elke
Abstract : We present a novel protocol that uses single‐cell force spectroscopy to characterize the bacteria‐to‐surface interactions involved in early steps of biofilm formation. Bacteria are immobilized as a monolayer by electrostatic interactions on a polyethylenimine‐coated silica bead, and the Escherichia coli‐ bead complex is then glued on a tipless cantilever. We validated our new protocol by comparing to earlier published methods using single bacteria, but in contrast to these, which carry out bacterial attachment to the bead after fixation to the cantilever, our protocol results in more reliable production of usable cell probes. Measurements of interactions of E. coli with bio‐inspired surfaces by single‐cell force spectroscopy yielded comparable detachment forces to those found with the previous methods.